Forks in the digital road key decisions in the history of the internet - Shackelford, Scott J. ca. 20./21. Jh; Bradner, Scott O. 1944- (Oxford University Press, 2024)
In Forks in the Digital Road, Scott J. Shackelford and Scott O. Bradner revisit the key decision points in the history of cybersecurity and Internet governance, revealing the alternative paths or "forks" that existed at the time and addressing the question of "what if?". They explain how things might have been different if other paths had been followed and offer practical ideas to help build a new vision of cyberspace that is as secure, private, efficient, and fun as possible. At a time when the future of cyberspace has never been more in doubt, the time is ripe to take both a look back, and ahead.
Keywords: Fehlinformation; Internet; Computersicherheit; Cyberspace; Geschichte